Determinacion de los hábitos alimentarios en tres Parroquias Urbanas La Matriz, Ignacio Flores, Juan Montalvo en el cantón de Latacunga en el periodo 2018-2019. - Alban Garcia, Bryan Diego (2019)
The present investigation was carried out in the canton Latacunga, in the parish Ignacio Flores, Juan Montalvo and the Matrix, to determine the eating habits of the inhabitants of the three parishes, knowing that in the province of Cotopaxi 34.2% of the total population does not have adequate food, so the objective of research is to determine and describe the consumption habits of the inhabitants of the parishes before identifying and building a sociogram connecting the different actors for which the methodology based on the approach of Pozo-Solís (2007) and with a stratified sampling for the application of 250 surveys and with results of 70% of inhabitants are women and 30% are men within the affected parishes in turn regarding the Intermediate age is from 41 to 50 years in 27% to what the level of education refers to in 39% in the aspect of the occupation 37% are private workers and at the same time their income The most prevalent in 41% is from 400 to 1000 dollars, the products that are consumed the most are fruits with 70%, vegetables with 49% and meat products with 34% that are the basic diet of the parishes already at the same time there is a high consumption of sugar in 54% and salt in 81% of consumption, that is, the feeding behavior is not adequate, in relation to agroecological products 59% do not consume and the other 31% do so in a few Sometimes, the inhabitants of the parishes where they usually buy their fresh produce are the popular markets in a 63, the relationship between the different actors with the patients is not satisfactory since there are no framed roads to help good food and high consumption of products such as sugar and salt mean that the diet is not in an optimal way.